2021
DOI: 10.1007/s12310-021-09434-w
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization: Investigating the Unique Contribution of Homophobic Bias on Adolescent Non-suicidal Self-injury and the Buffering Role of School Support

Abstract: Research on bullying victimization has expanded to specific forms of harassment based on discriminatory bias, which involve aggressive behavior targeting an individual's identity characteristics, such as sexual orientation and/or gender expression. Recent studies have documented elevated health risks associated with victimization based on homophobic bias, above and beyond general victimization. The aim of the current study was to test the unique contribution of homophobic victimization on adolescent non-suicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 96 publications
(147 reference statements)
0
8
0
Order By: Relevance
“…19 The IOC has similarly twice issued Scientific Consensus statements which have called for gay and bisexual young people to be protected in sport settings because it has found they are at uniquely 'high risk' (relative to their peers) of experiencing discrimination and all other forms of abuse. 9 11 Consistent with this conclusion, a recent international study (six countries; N=1173; ages [15][16][17][18][19][20][21] found more than half (52%) of the gay and bisexual boys had experienced homophobic victimisation in sport settings (eg, slurs, bullying, physical assaults). 20 Concerningly, the study found the teenage males who 'came out' as gay or bisexual to their teammates were the most likely to report these victimisation experiences.…”
Section: Original Researchmentioning
confidence: 83%
See 1 more Smart Citation
“…19 The IOC has similarly twice issued Scientific Consensus statements which have called for gay and bisexual young people to be protected in sport settings because it has found they are at uniquely 'high risk' (relative to their peers) of experiencing discrimination and all other forms of abuse. 9 11 Consistent with this conclusion, a recent international study (six countries; N=1173; ages [15][16][17][18][19][20][21] found more than half (52%) of the gay and bisexual boys had experienced homophobic victimisation in sport settings (eg, slurs, bullying, physical assaults). 20 Concerningly, the study found the teenage males who 'came out' as gay or bisexual to their teammates were the most likely to report these victimisation experiences.…”
Section: Original Researchmentioning
confidence: 83%
“…Rugby governing body leaders directly communicated with their volunteer coaches and the committees which run their community clubs and secured the participation by all nine clubs in the Australian state of Victoria with male (gender) 'under 18' (ages [16][17][18] and 'Colts' (ages 18-20 years) teams (table 1 provides participant details). Rugby's leaders felt securing participation in the study from the total population would help to overcome the noted problem 26 of selection bias with prejudice-reduction field trials (ie, the most problematic sports clubs choosing not to participate in the study).…”
Section: Recruitment and Participantsmentioning
confidence: 99%
“…Homophobic victimization is concerningly common in middle schools (Kosciw et al, 2018) and is associated with psychological distress for students, regardless of their sexual orientations (Poteat & Espelage, 2005;Poteat et al, 2012). A recent study also found that for high schoolers, targeted homophobic victimization was associated with nonsuicidal selfinjury (Esposito et al, 2021), and other researchers have demonstrated a significant association between homophobic victimization and suicidal thoughts and behaviors (Almeida et al, 2009;Rivers, 2001). Furthermore, researchers have clearly demonstrated that homophobic victimization is linked to poorer outcomes not only for youth who identify as homosexual but also those who identify as heterosexual; thus, homophobic victimization is a risk factor for all students.…”
Section: The Link Between Victimization and Depressionmentioning
confidence: 96%
“…This strategy arises from intra-(e.g., elevated physiological arousal) or interpersonal (e.g., deficits in social problem solving and communication) vulnerabilities that predispose them to perceive such events as particularly overwhelming and difficult to handle [19,20]. Despite the considerable heterogeneity between the studies, such as differences in the definitions of NSSI, sample recruitment and selection, and study design, a wide variety of stressful life events such as bullying victimization [21][22][23] and several psychopathological conditions, such as depression or anxiety [24][25][26] have been consistently associated with NSSI, also longitudinally [12,[27][28][29]. In an attempt to identify intrapersonal vulnerability factors that might contribute to the use of NSSI, other studies have related NSSI with personal characteristics that define individual differences, examining, for instance, the role of personality traits [e.g., 30,31], or self-regulation abilities such as impulsivity [32][33][34] and temperamental effortful control [35,36].…”
Section: Introductionmentioning
confidence: 99%